The life of Jesus, critically examined: Volume 2 - Strauß, David Friedrich (Cambridge library collection. Religion, 1846)
The German theologian David Friedrich Strauss (1808–1874) first published his highly controversial The Life of Jesus in three volumes between 1835 and 1836. This translation, by George Eliot, is based on the fourth German edition (1840). In this work Strauss applied strict historical methods to the New Testament gospel narratives and caused scandal across the Protestant world by concluding that all miraculous elements in the life of Jesus were mythical and ahistorical. In volume 2 Strauss applies modern historical criticism to 'de-mythologize' the idea of Jesus as Messiah; the narratives about the disciples; the discourses in the Synoptic gospels and the Fourth Gospel; the non-miraculous events; and the miracles' narratives. This is a key text of nineteenth-century theology that pioneered the application of historical and scientific methods to the study of religions and religious texts. It is essential reading for any student of the New Testament